METEOROLOGICAL AND HUMAN FACTORS INFLUENCE ON LEACHATE DYNAMICS - Vilda Grybauskiene; Gitana Vyciene (European Scientific Journal, ESJ, 2014)
The more urbanized society is, the larger the volumes of waste generated, and more problems are associated with their management. The aim of this article is to analyze Jarubaičiai landfill leachate generated content and dynamics of the factors causing this problem. This article analyzes Jerubaičiai landfill leachate resulting from the dynamics of the exchange of meteorological conditions and therefore increasing the amount of waste. This study was carried out from 05/15/2008 to 12/31/2008. The reference periods covers all seasons and are representative of Sightseeing meteorological conditions. Throughout the year, 6500 m3 leachate is formed at the Jerubaičiai landfill. The study found that during the year the amount of waste was 1050 tons of waste per weak. The landfill is covered by approximately. When the average air temperature is about - 10 °C, the leachate recycled content ranges from 40 to 140 m3. At the average temperature of 0 °C the leachate recycled content ranges from 250 - 270 m3 of leachate. During winter when the temperatures are below 0°C, 250-270 m3 of leachate transpires through the pile of waste. In summer, the total amount of precipitation was 52%, and the amount of leachatee setting-up to only 23% of the total filtrate. Correlation between air temperature and leechate r=0,784. It shows that air temperature strongly affects the amount of extracted filtrate. It was concluded that when the amount of waste in landfill increases, the amount of leachate discharged also increases at r = 0.641.